COMPARATIVE STUDY OF RELIGIOUS MODERATION BETWEEN THE YOUNGER GENERATION AND THE OLDER GENERATION - Fachruddin, Fachruddin; Yusuf, Ahmad Maulana (Universitas Islam Madura, 2025)
Religious moderation between the younger and older generations shows that both have unique characteristics and challenges. The younger generation, with an innovative spirit and access to information, can become agents of change that encourage tolerance and understanding between religious communities. Meanwhile, the older generation has experience and wisdom that are important to be used as a basis in efforts to strengthen religious moderation, the spirit of religious moderation to find common ground in religion. The method of this research is qualitative, data collection is interview, observation, and documentation. Seber data is the older generation and the younger generation to find and search for definitions related to research phenomena. The analysis technique used is the Descriptive Analysis technique. The results of the study show that the comparison shows that there are differences in religious moderation attitudes between generations. The younger generation is more inclusive, tolerant, and open to differences, which is largely influenced by interfaith interactions on social media. In contrast, older generations tend to maintain more conservative views, both from a religious perspective and the needs of life. The implication of this research is to understand the differences in mindsets and approaches to religious moderation between generations, so that it can be the basis for cross-generational dialogue programs to strengthen social harmony, Religious education in schools and religious institutions can adjust teaching methods to be more relevant to the needs of each generation.